2007
DOI: 10.1016/j.brainres.2006.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and caloric intake on glutathione redox state in different brain regions of C57BL/6 and DBA/2 mice

Abstract: The main purpose of the present study was to determine whether specific regions of the mouse brain exhibit different age-related changes in oxidative stress, as indicated by glutathione redox state and the level of protein-glutathionyl mixed disulfides. Comparison of 3-and 21-month-old mice indicated an age-related decrease in the ratio of reduced to oxidized glutathione (GSH:GSSG) as well as a prooxidizing shift in the calculated redox potential (ranging from 6 to 15 mV) in the cortex, hippocampus, striatum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 39 publications
(52 reference statements)
3
68
0
Order By: Relevance
“…Several studies have indicated that a disturbance in the redox state of an organism leads to aging and age-related diseases [3537]. Due to these unique features, Trx, along with thioredoxin interacting protein (Txnip), has been shown to play very important roles in physiology and its dysregulation could be involved in various diseases [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that a disturbance in the redox state of an organism leads to aging and age-related diseases [3537]. Due to these unique features, Trx, along with thioredoxin interacting protein (Txnip), has been shown to play very important roles in physiology and its dysregulation could be involved in various diseases [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the degree of age-associated oxidative stress/damage differs markedly among different regions of the brain , Rebrin, et al, 2007. Furthermore, studies of α-ketoglutarate dehydrogenase complex activity in neurodegenerative diseases have also suggested a dependence on brain region (Klivenyi, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine availability is rate-limiting for glutathione synthesis (Richman and Meister 1975;Suh et al 2004a). In this regard, there is considerable evidence that glutathione synthesis and glutathione tissue levels tend to decline in rodents and humans as they age (Suh et al 2004a;Rebrin and Sohal 2008;Rebrin et al 2007;Droge et al 2006;Sekhar et al 2011;Wang et al 2003;Lean et al 2005). This appears to reflect, in turn, an age-related decline in expression and function of the Nrf2 transcription factor (Suh et al 2004a;Suh et al 2004b;Ungvari et al 2011;Shih and Yen 2007).…”
Section: Glutathione Levels Decline During Agingmentioning
confidence: 99%
“…In aging mice, the content of reduced glutathione in the brain's cortex (hippocampus) and striatum is about 20-25 % lower than in young mice, whereas the ratio of reduced to oxidized glutathione is about 50 % as highindicative of a major increase in brain oxidative stress during aging (Rebrin et al 2007). Beginning at 18 months of age, rats were treated with a daily antioxidant cocktail-providing NAC, lipoic acid, and vitamin E; others were employed as controls (Thakurta et al 2014).…”
Section: Supplemental Nac In Aging Humans and Rodents Provides Versatmentioning
confidence: 99%